Analysis of the relationship between the gut microbiota enterotypes and colorectal adenoma - Lv, Miwei; Zhang, Jiawei; Deng, Jiaxin; Hu, Jiancong; Zhong, Qinghua; Su, Mingli; Lin, Dezheng; Xu, Tian; Bai, Xuhao; Li, Juan; Guo, Xuefeng (Frontiers in Microbiology, 2023)
Introduction The essence of enterotypes is to stratify the entire human gut microbiota, and dysregulation of gut microbiota is closely related to the development of colorectal adenoma. Enterotypes may therefore be a useful target for the prevention of colorectal adenoma. However, the relationship between gut microbiota and colorectal adenoma has not been fully elucidated. In this study, we aimed to analyze the differences in gut microbiome composition between adenoma and control populations. Methods We recruited 31 patients with colorectal adenoma and 71 non-adenoma controls. Patient demographics, risk factors, fecal samples from each subject were collected and metagenomic sequencing was performed. LEfSe analysis was used to reveal differences in intestinal microbiome composition. Multiple logistic regression analysis was used to determine the association between enterotypes and colorectal adenoma. Results The results showed that Prevotella enterotype (enterotype 4) is only present in adenoma group. Logistic regression analysis showed that Prevotella enterotype was an independent risk factor for colorectal adenoma. Discussion The Prevotella enterotype may increase the occurrence of colorectal adenoma through inflammatory association and interference with glucose and lipid metabolism in human body. In conclusion, the differences we observed between different enterotypes add a new potential factor to the development of colorectal adenoma.